INVESTIGATING ENGLISH NEED OF SHARIA BANK EMPLOYEES IN PAREPARE SOUTH SULAWESI - Zulfah Zulfah; Mujahidah Mujahidah (Universitas Islam Negeri Alauddin Makassar, 2018)
This study was aimed to investigate English need of sharia bank employees in Parepare. The design research was qualitative research. Subject of the research was 12 employees in 3 sharia banks in Parepare. Research data was collected by using interview. The findings showed that: (1) Islamic bank employees need English materials relate to banking, accounting, and computer application; and (2) Islamic bank employees need reading skills more than listening, speaking, and writing skills because they work more with English written documents. Bank employees also work with computer program. All instructions and terms in computer are in English. The employees need good pronunciation in English term of banking, accounting, and computer. They also need skills in correspondence in electronic letter or email.